TRI HITA KARANA: MODAL SPIRITUAL UNTUK MEWUJUDKAN PARIWISATA REGENERATIF DI BALI - Suasapha, Anom Hery (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2024)
Discussion on regenerative sustainability results from understanding that previous concepts of sustainability, the conventional and the contemporary sustainability, failed to achieve the sustainability agenda. The failure results from human behavior that considers themselves as having the right to use the environment to fulfill their needs. The urgency to satisfy their basic needs and, finally, their greed has resulted in an unsolvable problem: unsustainability. Sustainability is a behavioral matter, and behavior is a product of someone's understanding, attitude, value, beliefs, paradigm, or worldview. Therefore, to achieve sustainability, there should be a mindset change. As a form of contemporary spirituality, Tri Hita Karana can initiate change in the mindset concerning sustainability (inner-sustainability) through character education, so that regenerative sustainability and regenerative tourism in Bali can be achieved.